Annual Plan 1997-98 Volume-IV Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1997)
The State Council of Science and Technology was set up in the Andaman and Nicobar Islands on 22nd February,1982, reconstituted on 16th July, 1985 and started functioning on 8th July,1986 under the Chairmanship of the Lt.Governor of this Union Territory. To make the council more representative and broad based the Lt.Governor, Andaman and Nicobar Islands has been again pleased to reconstitute the Council on 31st January,1996.
Andaman and Nicobar Administration, Planning Department